Genre - text - interpretation: Multidisciplinary perspectives on folklore and beyond - Koski, Kaarina; Frog; Savolainen, Ulla (Studia Fennica Folkloristica, 2016)
"This book presents current discussions on the concept of genre. It introduces innovative, multidisciplinary approaches to contemporary and historical genres, their roles in cultural discourse, how they change, and their relations to each other. The reader is guided into the discussion surrounding this key concept and its history through a general introduction, followed by eighteen chapters that represent a variety of discursive practices as well as analytic methods from several scholarly traditions. This volume will have wide appeal to several academic audiences within the humanities, both in Finland and abroad, and will especially be of interest to scholars of folklore, language and cultural expression. "